GASER: genetic algorithm-based secure and energy aware routing protocol for sparse mobile ad hoc networks. (17th May 2019) - Kukreja, Deepika; Sharma, Deepak Kumar; Dhurandher, S.K.; Reddy, B.V.R.
Sparse mobile ad hoc networks are characterised by sparse node deployment and longer network partitions. This paper proposes a genetic algorithm-based secure and energy aware routing (GASER) protocol for sparse mobile ad hoc networks. By incorporating genetic algorithm with other methods, the GASER protocol selects the best path for routing the packets between source and destination in such a way that the selected path is shortest. Nodes of the selected path have highest message forwarding possibility among the other nodes of the network and have enough energy to receive and then forward messages. GASER avoids the nodes inducing grey hole/black hole attack in the network as it selects the next hop having more message forwarding probability thus making the routing protocol secure. Simulation results prove that GASER outperforms PROPHET, epidemic and spray and wait in terms of packet delivery ratio, average residual energy, overhead ratio and number of deceased nodes.